AN ALGORITHM OF MARKING IMAGES BASED ON THE VISUAL CRYPTOGRAPHY FOR PROTECTING FROM UNCONFIDENTIALITY INFORMATION DISTRIBUTION - A. A. Boriskevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An algorithm of marking image protecting from copying and illegal distribution of information based on the visual cryptography principles, representing an original image in form of the weighted binary plane set and binary marking mask in form of two shadow image is proposed. The modeling result have shown that the algorithm provides the high protection level of the images without changing of the image quality and qualitative reconstruction of the binary marking mask without the computational tools.